Ijtihad Sultan Muhammad Idrus Kaimuddin Ibnu Badaruddin Al Buthuni: Akulturasi Islam dan Budaya Kesultanan Buton - Melamba, Basrin; Siti Hafsah, Wa Ode (el Harakah: Jurnal Budaya Islam, 2014)
The coming of Islam in the Buton Sultanate has brought a change in the social, political, even in the intellectual aspects. It produced scholars with the thought or ijitihad as a blend of Islamic and local cultures. One of the scholars as well as Buton Sultan was Muhammad Idrus Kaimuddin Ibnu Badaruddin Al Buthuni (1824-1851). His thought or ijitihad found the essence of the concept of manners according to the teachings of the ancestors in kabanti Bula Malino. His several works became the guidance of the public and court authorities in the Sultanate of Buton which were basically rooted from the teachings of Islam. Kaimuddin’s thought in terms of ethics, morals, manners, or advice showed his horizons of knowledge and the depth of leadership thought. The magnitude of Islamic influence in some of his works proves the enduring process of Islamic acculturation done continuously and deeply since the era of Buton Islamic empire. Kaimuddin’s thought is essentially a formation process of Buton’s civilization centered on the palace and passed to Buton society in general through the process of cultural dialogue between Buton culture (Wolio) and Islam. Masuknya agama Islam di Kesultanan Buton, telah membawa perubahan dalam bidang sosial, politik, bahkan dalam aspek intelektual. Hal ini melahirkan ulama-ulama yang memiliki pemikiran atau ijitihad yang merupakan perpaduan budaya Islam dan budaya lokal. Salah satu ulama di Buton sekaligus sebagai Sultan yaitu Muhammad Idrus Kaimuddin Ibnu Badaruddin Al Buthuni (1824- 1851). Pemikiran atau ijitihad Sultan Kaimuddin menemukan esensi konsep tata krama menurut ajaran leluhur dalam kabanti Bula Malino. Beberapa karyanya menjadi tuntunan masyarakat dan penguasa kraton di Kesultanan Buton yang banyak bersumber dari ajaran Islam. Pemikiran dalam hal etika, moral, tata krama, maupun nasehat Sultan Kaimuddin menunjukkan cakrawala pengetahuan dan mendalamnya pemikiran seorang pemimpin. Besarnya pengaruh Islam dalam beberapa karya Sultan Kaimuddin membuktikan berlangsungnya proses akulturasi Islam secara berkesinambungan dan mendalam dari masa kerajaan Islam Buton. Hasil pemikiran Sultan Kaimuddin pada hakekatnya merupakan sebuah proses pembentukan peradaban Buton yang berpusat pada kraton dan ditularkan pada masyarakat Buton secara umum melalui dialog kebudayaan antara kebudayaan Buton (Wolio) dengan Islam.